Evaluating the Economic Resilience of Horticulture Against Food Inflation: A Price Transmission Analysis from Producers to Consumers of Strategic Commodities Using SP2KP Panel Data - Wartaka; Aisyah (Agriculture Journal, 2025)
The economic resilience of Indonesia's horticultural sector is frequently undermined by volatile food inflation and distributional inefficiencies. This study evaluates market resilience and price transmission mechanisms for strategic commodities—specifically chili and shallots—from producer to consumer levels. Utilizing weekly panel data from SP2KP and BAPANAS across 34 provinces (2022–2024), the research incorporates BMKG rainfall anomaly metrics within a Vector Error Correction Model (VECM) and Wald asymmetry tests. The findings confirm a stable long-term cointegration with a moderate weekly price adjustment rate of 24.5%. A pivotal discovery highlights significant asymmetric price transmission, where retail prices respond significantly faster to producer-level increases than to decreases, validating the "rockets and feathers" effect. Furthermore, climatic anomalies significantly intensify retail price instability. The study concludes that the Indonesian horticultural market remains structurally asymmetric and susceptible to exogenous shocks. These findings indicate that farm-gate price protection and supply chain efficiency are important factors shaping market resilience.